Estudo da erodibilidade de solos do reservatório da UHE Tucuruí - SILVA, Lucas Manoel da (Universidade Federal do Pará, 2020)
The Tucuruí Hydroelectric Power Plant, besides being the 5th largest hydroelectric plant in the world in generating capacity, transfers electric power to several Brazilian states and, having a reservoir of 2,917 km², is strongly subject to erosion. Several studies report the occurrence of erosive features near the its reservoir, besides being constantly subjected to laminar erosive actions in its drainage areas. In this work we carried out bibliographical surveys, field checks and direct and indirect analyzes of the erodibility of samples of the main soils of the Tucuruí HPP reservoir. Indirect analyzes employed semiempirical formulations based on physical and geotechnical characteristics of the, and the direct ones tested undisturbed samples under runoff, exposure to gradual and total water immersion processes, and under intense sample remoulding levels for evaluations in the Tropical Compacted Miniature - M.C.T. It was possible to notice a significant increase in the reservoir territorial occupation, favoring the exposure to erosive processes, and that the samples classified as Pedisol as Ultisol and Yellow Latosol presented average erodibility rates, as 0.0392 and 0.0323 g / cm² / min / Pa and low levels of disaggregation, while Red Latosol presented low erodibility as 0.002 g / cm² / min / Pa, medium to high levels of disaggregation and expansions, in the MCT methodology. These conclusions indicate that the agricutural activity in the area must grow crops that maintain the surface coverage of the first soil areas, and the prevention of uses that may disrupt and damage the last soil.